The role of CEUS in diagnosing tuberculous abscess of the right diaphragm - Wenzhi Zhang; Xiulei Yu; Jun Li; Lingling Wang; Jie Chu (BMC Infectious Diseases)
Abstract Purpose To evaluate the diagnostic value of contrast-enhanced ultrasound (CEUS) in detecting tuberculous diaphragmatic abscess (TDA) of the right diaphragm and provide a reference for its clinical diagnosis. Methods A retrospective analysis was conducted on 33 patients with right TDA confirmed via surgery and biopsy. The diagnostic accuracy of CEUS and routine ultrasound for detecting right TDA was compared. Results Among the 33 right TDA cases, the lesions primarily exhibited mixed and low echogenicity, with an orientation parallel to the diaphragmatic surface. Eighteen patients (54.5%) demonstrated the characteristic “crocodile mouth sign.” Heterogeneous enhancement was observed in most cases (24 patients) compared to homogeneous or no enhancement. The diagnostic accuracy of routine ultrasound for right TDA was 54.50% (18/33), whereas CEUS demonstrated a significantly higher accuracy of 78.78% (26/33) (χ2 = 4.364, P = 0.037). Conclusion CEUS provides valuable insights into the vascular characteristics of right TDA, with most cases showing mixed echogenicity and heterogeneous enhancement. The “crocodile mouth sign” was a distinctive feature, highlighting the utility of CEUS in improving diagnostic accuracy for right TDA.